Prediction, Suppression of Visual Response, and Modulation of Visual Perception: Insights From Visual Evoked Potentials and Representational Momentum - Kimura, Motohiro (Frontiers in Human Neuroscience, 2021)
When a visual object changes its position along with certain sequential regularities, the visual system rapidly and automatically forms a prediction regarding the future position of the object based on the regularities. Such prediction can drastically alter visual perception. A phenomenon called representational momentum (RM: a predictive displacement of the perceived final position of a visual object along its recent regular pattern) has provided extensive evidence for the predictive modulation of visual perception. The purpose of the present study was to identify neural effects that could explain individual differences in the strength of the predictive modulation of visual perception as measured by RM. For this purpose, in two experiments with a conventional RM paradigm where a bar was discretely presented in a regular rotation manner (with a step of 18° in Experiment 1 and a step of 20° in Experiment 2), visual evoked potentials (VEPs) in response to the regularly rotated bar were measured, and correlations between the magnitudes of RM and VEPs were examined. The results showed that the magnitudes of RM and central P2 were negatively correlated, consistently in both experiments; participants who showed a smaller central P2 tended to exhibit greater RM. Together with a previous proposal that central P2 would represent delayed reactivation of lower visual areas around the striate and prestriate cortices via reentrant feedback projections from higher areas, the present results suggest that greater suppression of delayed reactivation of lower visual areas (as indicated by smaller central P2) may underlie stronger predictive modulation of visual perception (as indicated by greater RM).